(untitled) (Research, Society and Development, 2021)
Traumatic bone cyst (TOC) refers to a rare lesion of the jaw, called by many authors as pseudocyst, in most cases the lesions are discovered by chance, in routine radiographs. It presents intraosseous, with a tenuous capsule or connective tissue without epithelium and most of the lesions are empty cavities, containing little serous or serosanguineous fluid, with an absent epithelial capsule. The aim of the study was to describe the clinical features of a rare case of traumatic bone cyst in an eight-year-old child, from diagnosis to case resolution. The first panoramic radiograph, taken right after the trauma, on 01/07/2020 shows the radiographic finding of a lesion, which was not diagnosed at the time. Due to the trauma, there was a fracture in the bone cortical, which was associated with this existing lesion. After one year, there was a recurrent inflammatory reaction, exposing the bone sequestration, new images, a detailed anamnesis, and especially a search for the initial image, determined that the lesion existed prior to the trauma that had occurred. According to the mother’s report, there were other, previous falls, making trauma the etiology of the injury. Through the surgical approach, a definitive diagnosis was possible, and the anatomopathological examination confirmed the diagnosis hypothesis being positive for TOC. The lower left canine erupting in an unfavorable position was referred to the orthodontics service. The dentist must have sufficient knowledge to differentiate and diagnose the most diverse cystic lesions, thus being able to proceed quickly and correctly with the resolution of cases, thus offering an accurate diagnosis and bone repair.